2015
DOI: 10.5194/acp-15-495-2015
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the chemical fate of the sulfate radical anion by reaction with sulfur dioxide in the gas phase

Abstract: Abstract. The gas phase reaction between SO4−(H2O)n and SO2, n = 0–2, is investigated using ab initio calculations and kinetic modelling. Structures of reactants, transition states and products are reported. Our calculations predict that the SO2SO4−(H2O)n cluster ion, which is formed upon SO2 and SO4−(H2O)n collision, can isomerize to SO3SO3−(H2O)n. The overall reaction is SO2 oxidation by the SO4−(H2O)n anionic cluster. The results show that SO4−(H2O)n is a good SO2 oxidant, especially at low relative humidit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 39 publications
1
19
0
Order By: Relevance
“…Calculated rate coefficients in Table are slightly overestimated both in gas and aqueous phases, on average by factors of 3.7 and 4.6, respectively. Underestimation of kinetic barriers is a known occurrence with DFT . However, hybrid and meta‐hybrid functionals such as B3LYP and M06‐2X provide a large improvement, particularly the M06‐2X functional, which exhibits an excellent performance on the calculation of standard thermochemistry properties .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Calculated rate coefficients in Table are slightly overestimated both in gas and aqueous phases, on average by factors of 3.7 and 4.6, respectively. Underestimation of kinetic barriers is a known occurrence with DFT . However, hybrid and meta‐hybrid functionals such as B3LYP and M06‐2X provide a large improvement, particularly the M06‐2X functional, which exhibits an excellent performance on the calculation of standard thermochemistry properties .…”
Section: Resultsmentioning
confidence: 99%
“…The exploration of this new functional was motivated by Jensen's theoretical work, in which it is pointed out that modeling of radical anions, such as SO 4 • — , must make use of functionals including a high percentage of exact exchange correlation. Moreover , CAM‐B3LYP has been found to perform well in the kinetic description of SO 4 • — radicals reacting with sulfur dioxide and with water clusters …”
Section: Computational Methodologymentioning
confidence: 99%
See 2 more Smart Citations
“…The sulfate radical ion is believed to react with unsaturated compounds to form organosulfates, a major component of secondary organic aerosol (Surratt et al, 2007;Surratt et al, 2008;Schindelka et al, 2013). Using first-principles calculations, it was demonstrated that SO4acts as a catalyst in SO2 oxidation to SO3 by O3 in the gas-phase and hence, plays a role in atmospheric aerosol formation (Tsona et al, 2015;Tsona et al, 2016). The chemistry of O2SOOis largely unknown but, is potentially important for sulfur chemistry and atmospheric aerosol formation.…”
mentioning
confidence: 99%